Macroeconomic Variables and Profitability in the Indonesian Islamic Banking Industry - Al Arif, Mohammad Nur Rianto; Rahmawati, Rahmi (El-Barka Journal of Islamic Economics and Business, 2021)
Profitability level is one of performance indicator in banking industry, including the Islamic banking industry. The purpose of this study is to analyse the short-run and long-run impact of macroeconomics variables to profitability in the Indonesian Islamic banking industry. The method that used in this paper is vector error correction models (VECM). The variables that used in this paper are industrial production index, inflation, exchange rate, the Bank Indonesia’s rate, and stock exchange composite index. The result shows that in the long-run, all of the macroeconomics variables affect significantly in profitability level. In the short-run, all macroeconomics variables do not  impact the profitability. This result implies that the macroeconomics variable had a time-lag to affect the profitability in the Indonesian Islamic banking industry. Salah satu indikator kinerja dalam industri perbankan termasuk industri perbankan syariah adalah tingkat profitabilitas. Tujuan dari penelitian ini ialah untuk menganalisis pengaruh variabel makroekonomi terhadap profitabilitas di industri perbankan syariah, baik dalam jangka pendek maupun jangka panjang. Metode yang dipergunakan dalam artikel ini ialah model vektor koreksi kesalahan. Variabel yang dipergunakan ialah indeks produksi industri, inflasi, nilai tukar, tingkat bunga Bank Indonesia, dan indeks harga saham gabungan. Hasil penelitian menunjukkan bahwa seluruh variabel makroekonomi berpengaruh dalam jangka panjang terhadap tingkat profitabilitas. Sedangkan, dalam jangka pendek seluruh variabel makroekonomi tidak berpengaruh terhadap tingkat profitabiltas. Hasil ini memberikan implikasi bahwavariabel makroekonomi memiliki jeda waktu untuk memengaruhi tingkat profitabilitas pada industri perbankan syariahdi Indonesia.